Iron deficiency anemia in children and adolescents - I.S. Tarasova ("Paediatrician" Publishers LLC, 2011)
The article presents data on incidence, etiology, pathogenesis and clinical presentation of iron deficiency anemia (IDA), principles of its diagnostics and treatment in children and adolescents. Author gives a description of iron drugs for oral and parenteral treatment that are frequently used in Russia, their advantages and shortcomings; principles of the control of their efficacy are described as well. Different types of prophylaxis are described: on population level (fortification), in the risk groups of IDA (supplementation), primary and secondary prophylaxis. The recommendation of American Academy of Pediatrics on prophylaxis of IDA in the most vulnerable group - infants and young children - is presented. Key words: children, adolescents, iron deficiency anemia, diagnostics, treatment, iron drugs, prophylaxis.